FORMULASI DAN EVALUASI SEDIAAN MASKER GEL PEEL-OFF EKSTRAK DAUN KELOR (Moringa oleifera L.) KOMBINASI VITAMIN E - Putra Chandra; Robiatun Rambe; Depi Yasinta (JURNAL FARMASI DAN MAKANAN, 2021)
Face mask is a beauty mask that serves as a carrier of active ingredients for skin health that is able to remove dead skin cells.. Peel-off face masks have several benefits, including being able toclean dirt on the face whileremoving dead skin cells, preventing skin damage caused by exposure to free radicals, such as acne and black patches, removing fine wrinkles due to premature aging, cleaning oil on the face and moisturizing and nourishing the skin.. The methods in this study use experimental. This research method is experimental. The study included, the creation of pell-off gel mask base orientation, formulating 3% moringa leaf ethanol extract and in combination with vitamin E with concentration variations of1%, 2%, 3%, 4% and 5% in pell-off gel maskpreparations, preparation evaluation tests including organoleptis, homogeneity, pH, scatter power, irritation tests on volunteer skin, as well as dry time, testing of pell-off gel masks. The results showed the evaluation test of the preparation of pell-off gel mask extract of moringa leaf combination of vitamin E in the homogeneity test of all homogeneous concentrations, the pH test showed all dosage concentrations met the pH requirement which ranged from 5-8, in the irritation test all preparations did not cause redness and on the dry time test all preparations met the requirements of under 30 minutes. The conclusion of ethanol extract of moringa leaves combination of vitamin E shows it can be used as an alternative to cosmetics and can be used as a reference for use as a natural cosmetic.